Variations in the C-unit of bedaquiline provides analogues with improved biology and pharmacology. Issue 1 (1st January 2020) - Sutherland, Hamish S.; Tong, Amy S.T.; Choi, Peter J.; Blaser, Adrian; Franzblau, Scott G.; Cooper, Christopher B.; Upton, Anna M.; Lotlikar, Manisha; Denny, William A.; Palmer, Brian D.
Graphical abstract: Highlights: Bedaquiline analogues with 3, 5-disubstituted-4-pyridyl C-units. High potency and attenuated hERG inhibition cf bedaquiline. 4–6.5 log units of bacterial clearance from lung in mouse model. Oral bioavailability generally 40–60%. Abstract: Analogues of the anti-tuberculosis drug bedaquiline, bearing a 3, 5-dimethoxy-4-pyridyl C-unit, retain high anti-bacterial potency yet exert less inhibition of the hERG potassium channel, in vitro, than the parent compound. Two of these analogues (TBAJ-587 and TBAJ-876) are now in preclinical development. The present study further explores structure-activity relationships across a range of related 3, 5-disubstituted-4-pyridyl C-unit bedaquiline analogues of greatly varying lipophilicity (clogP from 8.16 to 1.89). This broader class shows similar properties to the 3, 5-dimethoxy-4-pyridyl series, being substantially more potent in vitro and equally active in an in vivo (mouse) model than bedaquiline, while retaining a lower cardiovascular risk profile through greatly attenuated hERG inhibition.